Anaerobic digestion and recycling of kitchen waste: a review - Meng, Qingchen; Liu, Hongbo; Zhang, Haodong; Xu, Suyun; Lichtfouse, Eric; Yun, Yunbo (Environmental chemistry letters, 2022)
About 1.6 billion tons of food are wasted worldwide annually, calling for advanced methods to recycle food waste into energy and materials. Anaerobic digestion of kitchen waste allows the efficient recovery of energy, and induces low-carbon emissions. Nonetheless, digestion stability and biogas production are variables, due to dietary habits and seasonal diet variations that modify the components of kitchen waste. Another challenge is the recycling of the digestate, which could be partly solved by more efficient reactors of anaerobic digestion. Here, we review the bottlenecks of anaerobic digestion treatment of kitchen waste, with focus on components inhibition, and energy recovery from biogas slurry and residue. We provide rules for the optimal treatment of the organic fraction of kitchen waste, and guidelines to upgrade the anaerobic digestion processes. We propose a strategy using an anaerobic dynamic membrane bioreactor to improve anaerobic digestion of kitchen waste, and a model for the complete transformation and recycling of kitchen waste, based on component properties.